Influencia de la aplicación de la ficha socioeconómica en el tratamiento de los pacientes oncológicos atendidos en el IREN Norte, noviembre 2016. - Porras Zamora, Carmen Lucía de Jesús (2017)
The investigation of the thesis "influence of the application of the SOCIOECONOMIC tab in the treatment of oncology patients treated in the North IREN November 2016", emerges to need to know how influences the implementation of the tab socio-economic in the treatment of patients, since the study population are cancer patients carrying their treatment in the North Iren. The present study aims to determine the influence of the implementation of the socio-economic tab in the treatment of cancer patients attended in the Iren North, since the socio-economic tab is applied to users of which are evaluated in several areas: social, labor, educational, economic, sanitary, in order to be declared suitable, is to know all these details of the patient and their families. The methods used were the inductive, deductive, ethnographic and statistical method. And according to the techniques they were observing, unstructured interview, survey, informal talks and literature review; the same instruments as social tab, interview and questionnaires according to the treatment, application of the socio-economic tab, family characteristics, social problems and support networks. In Chapter I refers to the theory that was used and also acquired for the following research, presents the existing problems in the majority of users, as well as the assumptions and objectives raised. In chapter II manifests the methodological framework that has been used, covering the methods, techniques, instruments and sample universe which has the total number of users who formed a fundamental part of this investigative process. In chapter III announced the presentation of results which according to the different opinions of the users and the raised premises, their responses, showing statistics for each of the questions were. In chapter IV is reflected the discussion of results in which presents the contribution of authors giving reference to the issues, and the testimonies of patients, there is evidence demonstrating the expertise and experience of the researcher compared the different premises raised. The sample universe, was formed by 118 from cancer patients at the Regional Institute of neoplastic diseases; the results allow to affirm that the factors that have influenced the implementation of the socio-economic tab are individual and family characteristics, family relationship, the social problems in which networks of support that has the patient and family are immersed, and to its resolution all these factors have influenced in the trea